A deep X-ray view of the bare AGN Ark 120. III. X-ray timing analysis and multiwavelength variability. Issue 3 (8th November 2017) - Lobban, A P; Porquet, D; Reeves, J N; Markowitz, A; Nardini, E; Grosso, N
Abstract: We present the spectral/timing properties of the bare Seyfert galaxy Ark 120 through a deep ∼420 ks XMM–Newton campaign plus recent NuSTAR observations and a ∼6-month Swift monitoring campaign. We investigate the spectral decomposition through fractional rms, covariance and difference spectra, finding the mid- to long-time-scale (∼day–year) variability to be dominated by a relatively smooth, steep component, peaking in the soft X-ray band. Additionally, we find evidence for variable Fe K emission redward of the Fe Kα core on long time-scales, consistent with previous findings. We detect a clearly defined power spectrum which we model with a power law with a slope of α ∼ 1.9. By extending the power spectrum to lower frequencies through the inclusion of Swift and Rossi X-ray Timing Explorer data, we find tentative evidence of a high-frequency break, consistent with existing scaling relations. We also explore frequency-dependent Fourier time lags, detecting a negative ('soft') lag for the first time in this source with the 0.3–1 keV band lagging behind the 1–4 keV band with a time delay, τ, of ∼900 s. Finally, we analyse the variability in the optical and ultraviolet (UV) bands using the Optical/UV Monitor onboard XMM–Newton and the Ultra-Violet/Optical Telescope onboard Swift and search for time-dependent correlations between the optical/UV/X-ray bands. We find tentative evidence for the U -band emission lagging behind the X-rays with a time delay of τ = 2.4 ± 1.8 d, which we discuss in the context of disc reprocessing.